CRITICAL THINKING ANALYSIS OF SENIOR HIGH SCHOOL STUDENTS - Rambe, Aswiyanti Ami Yanda; Chastanti, Ika; Sari, Novi Fitriandika (Research and Development Journal of Education, 2025)
Critical thinking skills are crucial in 21st-century education, which is filled with various challenges. This research uses a combination of quantitative and descriptive approaches. Its aim is to examine and compare students' analytical thinking capabilities at the secondary school level specializing in Social Sciences with those studying Mathematics and Science Data is gathered through observations and surveys that cover several. The research results revealed that students in Social Sciences major have much better critical thinking skills compared to students in the Mathematics and Science majors. Students in the Social Sciences major were also better at evaluating and making critical decisions, but students in the Mathematics and Science majors were worse at analytical thinking. These findings indicate that the curriculum and teaching methods in Compared to the Mathematics and Natural Sciences majors, The Social Sciences major promotes Strengthening critical thinking skills is very important. It is recommended that the MIPA study program update its teaching approach with more emphasis on developing evaluation and critical thinking skills.